Pemberdayaan Masyarakat di Desa Berbasis Komunitas - Ambarsari, Retno; Dewi, Rosanti Kurnia; Darmadja, Sobar (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Community empowerment is the process of giving individuals the capacity and autonomy to realize their inherent potential. The purpose of this research is to investigate community empowerment tactics based on community activities and to identify variables that limit community empowerment. This form of research is qualitatively descriptive and employs a case study design. Through in-depth interviews, observation, and recording, qualitative data was gathered and evaluated. The findings indicate that several strategies have been implemented in community empowerment, including increasing public awareness of the significance of groups and communities and addressing several obstacles that impede community empowerment, such as a lack of community participation, a lack of knowledge and capital, a lack of assistance and counseling, and the absence of the village government. This research suggests numerous alternate activities for enhancing the application of community empowerment and group members' knowledge and abilities. During the execution of this plan, numerous impediments to community empowerment were identified, notably a lack of community engagement, a lack of expertise and capital, a lack of support and counseling, and a lack of village government involvement. And highlighted that, in essence, village empowerment has a strategic component to explore the potential and capability of development and to offer the creation, execution, monitoring, and evaluation of the topic of local activities. This demonstrates the function and well-being of the village community itself.